Zinc protoporphyrin assays in patients with alpha and beta thalassaemia trait. Issue 3 (March 1994) - Tillyer, M L; Tillyer, C R
Abstract : AIMS--To determine the value of the red cell distribution width (RDW) and erythrocyte zinc protoporphyrin (ZPP) concentration in discriminating between iron deficiency, and beta and alpha thalassaemia in a mixed urban Asian population. METHODS--The RDW and ZPP concentrations were measured in 1412 subjects attending for outpatient phlebotomy, with classification into diagnostic groups on the basis of haemoglobin, mean cell haemoglobin, ferritin, HbA2 and haemoglobin electrophoresis. RESULTS--Non-parametric 95% reference ranges for RDW were 11.7-15.7% and for ZPP 38-104 mumol/mol haem. Both RDW and zinc protoporphyrin rose with increasing severity of iron deficiency, but were also raised in significant numbers of subjects with beta and probable alpha thalassaemia. CONCLUSIONS--Measurements of RDW and ZPP do not differentiate between alpha or beta thalassaemia trait and moderate degrees of iron deficiency (hypochromasia without anaemia). ZPP is a more accurate indicator of iron deficiency than RDW and concentrations above 150 mumol/mol haem strongly suggest iron deficiency, usually with anaemia, rather than thalassaemia.